Study of the behavior of concrete under triaxial compression - Sfer, Domingo (2002)
An experimental study of the confined compression behavior of concrete has been performed using 150x300 mm cylindrical specimens subjected to hydrostatic pressure in a triaxial cell and axial loading through a servo-hydraulic testing machine. A confining stress range of 0 to 60 MPa (about twice the uniaxial compressive strength) was employed to obtain the brittle-ductile transition behavior of the material. The increase in confining pressure leads to a change in the mode of failure and an increase in the maximum axial load-carrying capacity. It is seen that, at zero or low confinement, there is distributed microcracking and several macrocracks, and the response exhibits a well-defined peak and subsequent softening. At high confinements, relatively large axial and transversal strains of over 10% have been obtained, with monotonically increasing loads leading to horizontal plateaus. There is no distributed cracking and failure occurs with the propagation of few macrocracks. In general, the observed trends confirm and extend previous results reported in the literature. Optical microscopy shows extensive microcracking, especially in the aggregates, and poce collapse at high confinement. A preliminary interpretation of the results based on the theory of elastoplasticity is also presented.